Evaluation of Different Lentil Cultivars in Lowland Rice Fallow under No-Till System for Enhancing Cropping Intensity and Productivity - LAYEK, JAYANTA; CHOWDHURY, SAMIK; GI, RAMKRUSHNA; DAS, ANUP (Indian Journal of Hill Farming, 2015)
Lentil is a potential crop for crop diversification and enhancing productivity of rice based cropping systems. Thus, a field experiment was conducted during 2012-13 and 2013-14 to evaluate the performance of lentil varieties under no-till condition after harvest of lowland rice. Twenty lentil (Lens culinaris) cultivars were obtained from various sources (Indian Institute of Pulses Research, Kanpur, ICAR Research Complex for NEH Region, etc.) and tested in rice fallow under no-till condition with residual soil moisture. One lifesaving irrigation was given during flowering stage for better growth and yield of lentil. Results revealed that in-terms of number and biomass of root nodules, IPL 406 (20.4 and 47.6 mg, respectively) and DPL 62 (20.2 and 46.9 mg, respectively) were the most efficient cultivars. Number of pods/plant were significantly higher in IPL 406 (54.44) followed by DPL 62 (52.29) and L-303 (49.04) than rest of the cultivars. The weight of 1000 seeds was the highest in DPL 81 (36.0g) followed by L-307 (35.7g). The seed yield was the highest in DPL 81 (1.59 t/ha) and was at par with IPL 406 (1.55 t/ha) and DPL 62 (1.53 t/ha) all of which were significantly higher than those of other cultivars. Most of the cultivars matured in about 110-115 days with very few maturing in about 118-119 days. Thus, the study revealed the opportunity of lentil cultivation in lowland rice fallow with appropriate technologies in mid-altitude of Meghalaya.